Volunteering across contexts: comparing attitudes toward volunteering with prisoners and people with mental illness - Dá Mesquita, Lara; Oliveira, Jaime; Pinto da Costa, Mariana (Frontiers in Public Health, 2024)
Introduction Volunteering represents an opportunity for social transformation and social cohesion. Portugal is one of the European countries with fewer volunteering initiatives. Generally, society distances itself from individuals with mental illness and prison inmates, therefore, stigma becomes one of the barriers to social reintegration. However, volunteering can be a beneficial intervention helping individuals in their reintegration. Objectives This study aims to compare the differences and similarities in the attitudes of volunteers toward volunteering with people with mental illness and prisoners. Methods A supplementary qualitative secondary analysis was conducted using transcripts from 39 semi-structured individual interviews with volunteers regarding support of inmates in prison and two focus groups with volunteers regarding support of people with mental illness. Data analysis was conducted through an inductive thematic analysis. Results Four themes emerged from the analysis: ‘Volunteer motivation and characteristics’, ‘Volunteer’s role’, ‘Volunteering relationship and its impact’, and ‘Challenges faced by volunteers’. There were several similarities between the perspectives toward volunteering in prisons and in mental health care, including the need for specific training in the area and the positive attitudes and behaviors of both groups of volunteers toward volunteering with the individuals supported. The differences were related to the characteristics necessary to be a volunteer, the activities carried out with the individuals supported and the difficulties faced by volunteers. Conclusion These findings show overall positive attitudes toward volunteering in mental health and in prisons.